A CLINICAL STUDY ON THE EFFICACY OF SITAMANDOOR ON AMLAPITTA - Bhojak, Poonam; S., Amita.; Mitt, J.G.; Patil, M.C. (International Journal of Ayurveda and Pharma Research, 2015)
Acharya Caraka & Kashyapa have explained that Amlapitta is mainly caused by dietetic pattern, mental stress and strain which are related to our digestion. The occurrence involves the GIT & chiefly Kapha & Pitta Dosha. The symptoms like Gastritis, peptic disorders, hyperacidity, hyperchlorhydria condition resemble that of Amlapitta. Aim & Objective: To evaluate the efficacy of Sitamandoor in Specific patients of Amlapitta Study Design: The study was conducted on total 18 patients of Amlapitta who completed the treatment all along the study period. The patients were selected from the OPD of DGMAMC&H, Gadag for respective clinical trial. Assessment criteria: Criteria of assessment are set aside on the basis of relief in the signs and symptoms of Amlapitta both subjective and objective parameters. Results: Among 18 patients 9 responded moderately, 3 markedly improved and 5 responded well to the treatment. Interpretation & Conclusion: Though the criteria of assessment & statistical analysis reveal the effect of the study but the fact that the mode of action of the drug is the base of the relief in signs & symptoms cannot be ignored. Conclusively the treatment was satisfactorily effective in the patients.